Protection of cumulus cells following dehydroepiandrosterone supplementation. (1st February 2017) - Lin, Li-Te; Wang, Peng-Hui; Chen, San-Nung; Li, Chia-Jung; Wen, Zhi-Hong; Cheng, Jiin-Tsuey; Tsui, Kuan-Hao
Abstract: Background : Growing studies have demonstrated that dehydroepiandrosterone (DHEA) may improve fertility outcomes in poor ovarian responders (PORs). The aim of this study was to compare clinical outcomes and cumulus cell (CC) expression before and after DHEA treatment in PORs undergoing in vitro fertilization (IVF) cycles. Methods : Six patients with poor ovarian response were enrolled in the study according to Bologna criteria. DHEA was supplied at least 2 months before patients entered into the next IVF cycle. Expression of apoptosis-related genes in CCs was determined by quantitative real-time PCR. Mitochondrial dehydrogenase activity of CCs was assessed by cell counting kit-8 assay. Results : Metaphase II oocytes, maturation rate, embryos at Day 3, and fertilization rate significantly increased following DHEA treatment. Expression of cytochrome c, caspase 9, and caspase 3 genes in CCs were significantly reduced after DHEA therapy. Additionally, increased mitochondrial activity of CCs was observed following DHEA supplementation. Conclusions : DHEA supplementation may protect CCs via improved mitochondrial activity and decreased apoptosis, leading to better clinical outcomes in PORs.